2010
DOI: 10.1007/s13304-010-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal metastases from adenocarcinoma of the esophagogastric junction: adrenalectomy and long-term survival

Abstract: Treatment of adrenal metastases from cancer of the esophagogastric junction (EGJ) is not defined. The aim of the present work is to analyze retrospectively our experience in treating patients with adrenal metastases from EGJ adenocarcinoma. 102 patients with Siewert 1 or 2 EGJ adenocarcinoma underwent esophagectomy between May 2001 and Jan 2009. Five patients were diagnosed an adrenal metastases from EGJ adenocarcinoma, synchronous (s) in one and metachronous (m) in four, in the latter 11 months (mean) after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…In a case series of 5 patients, only one 79-year-old patient presented with no signs of other metastasis and was treated, 13 months after esophagectomy for a Siewert type 2 carcinoma of the esophagogastric junction, with a laparoscopic left adrenalectomy. He died with progressive disease 28 months later [ 31 ]. O’Sullivan et al reported a case of a 50-year-old man who was submitted to an open right adrenalectomy 4 years after a two-stage esophagectomy for a Siewert type 1 cancer of the esophagogastric junction and remained disease-free for over 4 years postadrenalectomy [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a case series of 5 patients, only one 79-year-old patient presented with no signs of other metastasis and was treated, 13 months after esophagectomy for a Siewert type 2 carcinoma of the esophagogastric junction, with a laparoscopic left adrenalectomy. He died with progressive disease 28 months later [ 31 ]. O’Sullivan et al reported a case of a 50-year-old man who was submitted to an open right adrenalectomy 4 years after a two-stage esophagectomy for a Siewert type 1 cancer of the esophagogastric junction and remained disease-free for over 4 years postadrenalectomy [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fumagalli et al and Dellaportas et al reported that particularly those with adenocarcinoma of the esophagogastric junction benefit from adrenalectomy in case of the only site of metastasis beyond lymphnodal disease (6,7). Chemotherapy should also be considered before adrenalectomy but, due to the severity of the symptoms related to dysphagia, we planned the surgical intervention as early as possible for this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although substantial evidence exists to support surgical resection as the optimal treatment for liver or lung metastasis from colorectal cancer [ 11 ], data evaluating the role of local therapy for metastatic gastric cancer are limited and controversial. Some reports of patients with gastric cancer and synchronous metastasis demonstrate long-term survival following complete surgical resection of the metastatic lesions and appropriate systemic chemotherapy [ 3 4 5 6 7 8 9 10 ]. In addition, local therapy (such as surgical resection, radiofrequency ablation, or hepatic arterial infusion chemotherapy) for the treatment of liver metastasis from primary gastric cancer has been shown to be potentially curative in carefully selected patients [ 6 7 8 9 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, prolonged patient survival has been associated with the availability of new chemotherapeutic regimens and many reports have shown improved survival following local treatment of metastatic lesions from gastric cancer [ 3 4 5 6 7 8 9 10 ], particularly surgical resection for patients with liver metastases [ 6 7 8 9 10 ]. However, reports of long-term survival after repeated local therapy for recurrent metastatic lesions from gastric cancer are still extremely rare.…”
Section: Introductionmentioning
confidence: 99%